The ribbed drapery of the Puerto Princesa Underground River (Palawan, Philippines): morphology and genesis - Paolo Forti; Giovanni Badino; José Maria Calaforra; Jo De Waele (International Journal of Speleology, 2017)
During the 2011 speleological expedition to the Puerto Princesa Underground River (Palawan, Philippines) a drapery characterized by several close-to-horizontal ribs has been noticed. Even without sampling and analyzing its internal growth layers, a detailed morphological study allowed to present a possible genetic model. The presented model helps to explain its evolution, which is mainly controlled by variation in water flow as a consequence of the Palawan climate. When validated by further analyses, the same genetic mechanism could define also the evolution of the very common but still unexplained complex flowstones, which exhibit several close-to-horizontal steps, widenings and narrowings along their growth axis.